Influence of Livelihood Capital on Coastal Fishermen's Intentions for Livelihood Tourism Transformation: The Mediatory Role of Risk Cognition - Chen Yangle; Wang Tianyi; Tang Xiaoqian (Redai dili)
The transformation of livelihood tourism is a key factor for fishermen in optimizing their livelihood strategies and achieving sustainable development. This is an effective strategy for improving the marine ecological environment, protecting marine biodiversity, and supporting the development of destination tourism. Recent research has demonstrated that the transformation of livelihood tourism is one of the most promising strategies for rural tourism destinations. In addition to considering the individual livelihood capital status, livelihood tourism transformation must assess the risks and uncertainties that may exist. Based on sustainable livelihood and prospect theories, this study considered the unique characteristics of coastal fishermen and established a livelihood capital evaluation index system for them. An integrated model was constructed using livelihood capital, risk cognition, and livelihood tourism transformation intention. An empirical test was conducted using 310 valid questionnaires obtained from a survey of fishermen in Tanmen Town, Qionghai City, Hainan Province, China. The results were as follows. (1) The overall level of sustainable livelihood among coastal fishermen was relatively low, with significant differences in its dimensions. The level of natural capital was relatively high, with a livelihood capital value of 0.646. Human and material capital were at moderate levels, with livelihood capital values of 0.555 and 0.510, respectively. Financial and social capital levels were relatively low, with livelihood capital values of 0.280 and 0.192, respectively. The livelihood capital levels of coastal fishermen were generally lower than those of farmers in other regions. (2) Livelihood capital significantly influenced fishermen's willingness to engage in livelihood tourism transformation, with human, material, and social capital showing significant positive effects, consistent with previous research findings. Natural and financial capital had significant negative effects. Owing to the unique attributes of coastal fishermen, the impact of financial capital on their willingness to engage in livelihood tourism transformation differedO from previous research conclusions. (3) Risk cognition had an intermediate effect between human, social, and financial capital on livelihood tourism transformation intention. The mediating effects of natural and material capital on livelihood tourism transformation intention were not significant. This study revealed the relevant factors influencing livelihood tourism transformation intention. It innovatively discusses the mediating role of risk perception in the influence of livelihood capital on livelihood tourism transformation intention by combining it with prospect theory. It deepens the understanding of existing studies on the livelihood level and structure of coastal fishermen and enriches the application of prospect theory in tourism research. It provides theoretical support and a scientific basis for improving the livelihood level of fishermen and the driving force of livelihood tourism transformation, offering new insights for optimizing livelihood strategies and sustainable development of coastal fishermen.